The valley = Estampas del valle - Hinojosa, Rolando (Arte Público Press, 2014)
In these vignettes set in the fictional county of Belken along the Texas-Mexico border in the early to mid-twentieth century, Rolando Hinojosa sketches a landscape of Mexican Texans and Anglo Texans living side by side, in good times and bad.